Expermental Studies of quantitative evaluation using HPLC and safety of Sweet Bee Venom - Ki Rok Kwon; Ching Seng Chu; Hee Soo Park; Min Ki Kim; Bae Chun Cha; Eun Lee (Korean Pharmacopuncture Institute, 2007)
Objectives : This study was conducted to carry out quantitative evaluation and safety of Sweet Bee Venom. Methods : Content analysis was done using HPLC, measurement of LD50 was conducted intravenous, subcutaneous, and intra-muscular injection to the ICR mice. Results : 1. According to HPLC analysis, removal of the enzymes containing phospholipase A2 was successfully rendered on Sweet Bee Venom. And analyzing melittin content, Sweet Bee Venom contained 12% more melittin than Bee Venom. 2. LD50 of ICR mice with Sweet Bee Venom was more than 20mg/kg in subcutaneous injection and intravenous injection, between 15mg/kg and 20mg/kg in muscular injection. 3. LD50 of ICR mice with Bee Venom was between 6 and 9mg/kg in subcutaneous injection and intravenous injection, and more than 9mg/kg in muscular injection. Conclusion : Above results indicate that Sweet Bee Venom was more safe than Bee Venom and the process of removing enzymes was well rendered in Sweet Bee Venom.